A review article on the photocatalytic degradation of atrazine by potential catalysts - Fawad Ahmad; Sabeen Tahir; Ayesha Wali; Muhammad Imran Khan; Abdallah Shanableh (Next Materials, 2025)
Atrazine, a persistent herbicide with endocrine-disrupting properties, poses significant environmental and health risks. Its widespread use and persistence in aquatic ecosystems necessitate effective remediation strategies. Photocatalytic degradation, a promising green technology, utilizes light energy to degrade pollutants into less harmful substances. This study systematically investigates the photocatalytic degradation of atrazine using a variety of photocatalysts, including TiO2, boron-doped TiO2, ZnIn2S4-based catalysts, indole-3-acetic acid-montmorillonite clay composites, ZnO-based catalysts, ZnO/GO composites, Pd/ZnWO4 nanocomposites, and zinc-doped cadmium aluminum ferrite. Boron-doped TiO2 achieved a degradation efficiency of 94.7 % within 180 min under visible light. The influence of key parameters such as catalyst concentration, pH, initial atrazine concentration, and light intensity on the degradation process was systematically examined. A novel aspect of this research lies in the comparative analysis of diverse photocatalysts, enabling the identification of optimal conditions for efficient atrazine removal. High-performance liquid chromatography (HPLC) and total organic carbon (TOC) analyses confirmed both primary degradation and mineralization of atrazine. The findings of this study offer valuable insights into the potential application of photocatalytic technology for the remediation of atrazine-contaminated water bodies. By optimizing reaction conditions and selecting suitable photocatalysts it is possible to achieve effective and sustainable removal of this persistent pollutant.